1. a)5 < m < 15; 5*1/5 < 1/5 m < 15*1/5; 1 < 1/5 < 3
b) 5 < -2m < 15; 5*(-2) < -2m < 15*(-2); -10 < -2m < -30; -30 < -2m < -10
c) 5 < m-6 < 15; -5+6 < m-6 < -15+6 ; 1 < m-6 < -9; -9< m-6 < 1
2. a) 2.6 <√7 <2.7; 2.6*2 < 2√7 < 2.7*2 ; 5.2 < √7 < 5.4
b)- 2.6 <-√7 < -2.7; -2,7 < -√7 < -2,6
c) 2.6 <√7 <2.7; 2+2.6 < 2+√7 < 2+2.7; 4.6 < √7 < 4.7
d)2.6 <√7 <2.7; 3-2.6 < 3-√7 <3-2.7; 0.4 <;3-√7 <0.3; 0.3 < 3-√7 < 0.4
Вот накалякал. Разбирайся :)
xy/(x+y) = 5
xz/(x+z) = 7
yz/(y+z) = 9
xy = 5x + 5y
xz = 7x + 7z
yz = 9y + 9z
x(y-5) = 5y
x = 5y/(y-5)
5yz/(y-5) = 35y/(y-5) + 7z
5yz = 35y + 7z * (y-5)
5yz = 35y + 7yz - 35z
2yz + 35y = 35z
y(2z + 35) = 35z
y = 35z/(2z + 35) = z/(2z/35 + 1)
35z^2/(2z + 35) = 315z/(2z + 35) + 9z
35z^2 = 315z + 9z*(2z + 35)
35z^2 = 315z + 18z^2 + 315z
17z^2 = 630z
z=630/17
y = 35*630/(2*630/17 + 35)/17 = 35*630/(1260 + 595) = 22050/1855 = 630 / 53
x = 5*630/(630/53 - 5)/53 = 5*630/((630/53 - 5)*53) = 5*630/365 = 630/73